Agreements and benefits in emerging ocean sectors: Are we moving towards an equitable Blue Economy?. (1st April 2022) - Cisneros-Montemayor, Andrés M.; Ducros, Anna K.; Bennett, Nathan J.; Fusco, Leah M.; Hessing-Lewis, Margot; Singh, Gerald G.; Klain, Sarah C.
Abstract: Transitioning to a Blue Economy that prioritizes social equity will be challenging in ocean sectors but could be comparatively easier for newer industries where appropriate guidelines can be followed from the start. We focus here on two emerging ocean sectors—blue carbon and ocean energy—and an evaluation of benefit-sharing agreements at operational sites, and the recipients and types of these benefits. This is an initial yet useful gauge of progress towards integration of social equity concerns as envisioned under a Blue Economy. The number ( n = 84) and scale of ocean energy sites is rapidly increasing but highly concentrated in a few regions. The ocean energy sector is currently focused on serving grids in urbanized areas and reducing national emissions, and economic benefit-sharing mechanisms with local residents are less common (35% of all sites). However, some cases show how local communities can be better included in the planning and implementation of ocean energy, including negotiation of subsequent economic benefits. Despite widespread interest in blue carbon, we found very few ( n = 4) operational sites; nonetheless, these were deeply involved with and often led by local communities who are the main beneficiaries. Voluntary public and corporate social responsibility actions are useful, but government regulation must play an essential role in requiring equitable processes and supporting equitable outcomes, similar to now-standard environmental regulations to avoid negative impacts and increase the likelihood of ecological sustainability. Emerging ocean sectors have a unique opportunity to advance social equity and environmental sustainability within Blue Economies, but this will be much more easily achieved if equity guidelines are prioritized and mandated so that business-as-usual practices do not become entrenched.